Functional anatomy and ion regulatory mechanisms of the antennal gland in a semi-terrestrial crab, Ocypode stimpsoni - Tsai, Jyuan-Ru (The Company of Biologists, 2014)
Brachyuran crabs from diverse habitats show great differences in their osmoregulatory processes, especially in terms of the structural and physiological characteristics of the osmoregulatory organs. In crustaceans, the antennal glands are known to be important in osmoregulation, and they play a functional role analogous to that of the vertebrate kidney. Nevertheless, the detailed structure and function of the antennal glands in different species have rarely been described. The aim of this study is to investigate the role of the antennal gland in ion regulation by examining the ultrastructure of the cells and the distribution of the ion regulatory proteins in each cell type in the antennal gland of a semi-terrestrial crab. The results showed that Na(+), K(+)-ATPase activity significantly increased in the antennal gland after a 4-day acclimation in dilute seawater and returned to its original (day 0) level after 7 days. Three major types of cells were identified in the antennal gland, including coelomic cells (COEs), labyrinthine cells (LBRs) and end-labyrinthine cells (ELBRs). The proximal tubular region (PT) and distal tubular region (DT) of the antennal gland consist of LBRs and COEs, whereas the end tubular region (ET) consists of all three types of cells, with fewer COEs and more ELBRs. We found a non-uniform distribution of NKA immunoreactivity, with increasing intensity from the proximal to the distal regions of the antennal gland. We summarise our study with a proposed model for the urine reprocessing pathway and the role of each cell type or segment of the antennal gland.